2016
DOI: 10.1007/s11051-016-3483-1
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of gold nanostars using plant polyphenols for cancer photoacoustic imaging and photothermal therapy

Abstract: Branched plasmonic nanostructures have been found to exhibit strong enhancement of the electromagnetic field surrounding their multibranched petals. This feature endows them with improved performance in catalysis, surface-enhanced Raman scattering, photoacoustic imaging, and photothermal therapy. Albeit several synthesis techniques have been developed, the precisely controlled growth of highly branched nanostructures with a one-pot surfactant-free procedure is still challenging. Herein, we present a simple see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…A seedless synthesis of nanostars that employed glucosamine or glucamine without any additional surfactants or shape-directing agents was reported by Moukarzel et al, (Figure 5b) [70]. Similarly, homogeneous nanostars were produced by using gallic acid (Figure 5c) [71]. Kircher et al developed a seed-mediated method to produce various shapes of nanoparticles using only alkaline hydrogen peroxide and gold chloride, demonstrating the capability to controllably generate various shapes and sizes of nanostars by closely tuning the reaction kinetics (Figure 5d) [72].…”
Section: Surfactant-free Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…A seedless synthesis of nanostars that employed glucosamine or glucamine without any additional surfactants or shape-directing agents was reported by Moukarzel et al, (Figure 5b) [70]. Similarly, homogeneous nanostars were produced by using gallic acid (Figure 5c) [71]. Kircher et al developed a seed-mediated method to produce various shapes of nanoparticles using only alkaline hydrogen peroxide and gold chloride, demonstrating the capability to controllably generate various shapes and sizes of nanostars by closely tuning the reaction kinetics (Figure 5d) [72].…”
Section: Surfactant-free Methodsmentioning
confidence: 88%
“…Copyright 2011 American Chemical Society; (b) glucosamine, adapted from ref [70]. with permission from The Royal Society of Chemistry; (c) gallic acid[71], (d) hydrogen peroxide, adapted with permission from ref [72],. Copyright 2017 WILEY-VCH; (e) dopamine, adapted from ref [73].…”
mentioning
confidence: 99%
“…The latter has been confirmed by several studies that validate their application for tumor hyperthermia, with therapeutic responses for a laser power density of 0.2 W/cm 2 , the lowest reported pulsed lasers intensities (PW) . In addition, their use as active agents for photothermia has been reported, which combined with the surface-enhanced Raman spectroscopy (SERS) techniques and photoacoustic images, have allowed therapy and imaging to be carried out simultaneously. , With such a variety of geometries and sizes, the choice of nanostructures and their synthesis and modifications are fundamental in the development of nanostructures for medical applications …”
Section: Introductionmentioning
confidence: 87%
“…17 In addition, their use as active agents for photothermia has been reported, which combined with the surface-enhanced Raman spectroscopy (SERS) techniques and photoacoustic images, have allowed therapy and imaging to be carried out simultaneously. 18,19 With such a variety of geometries and sizes, the choice of nanostructures and their synthesis and modifications are fundamental in the development of nanostructures for medical applications. 20 Herein, we report the synthesis and biomedical applications of a theragnostic Au-based NPs with absorption in the NIR.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles are the most commonly used plasmonic PA contrast agents . They can be synthesized as spheres, cubes, plates, rods, ,, cages, shells, bipyramids, and stars. , The tips and edges lead to enhancement of the electromagnetic field as electron density increases at the tips. Simulations have shown that sharper tips have a higher μ a compared to rounded tips .…”
Section: Shape and Size Controlmentioning
confidence: 99%